Canadian Mennonite Narratives as Historiographic Ethnofictions of Space - Korkka Janne (Vandenhoeck & Ruprecht, 2025)
When Janice Kulyk Keefer proposed the concept of historiographic ethnofiction in 1995, she drew on her own experience of “the problems and traumas and unacknowledged possibilities that compose the true site of [her] ethnicity” (“Coming Across”). She desires to depart from established ways to read, write, and transmit ethnicity, and in that project repeatedly invokes spatial concepts in both concrete and metaphoric ways. Ideas of ethnicity may comprise of narratives of “some enchanted world out of place and time” (“Coming Across”), narratives that I read to be idealised but inevitably linked to someone’s memory of lived space. As Kulyk Keefer talks of her own ethnicity as a “site”, she further anchors discourses of ethnicity in a discourse of spatiality.
Inspired by Kulyk Keefer, this article explores selected Canadian Mennonite narratives as historiographic ethnofictions of space. I propose they showcase a distinct strand of ethnofiction concerned with place and space that began with the writings of Rudy Wiebe, in particular his 1970 novel The Blue Mountains of China which looked at a Mennonite past and present in Russia, South America, and Canada. The novel no longer perpetuates the once historical and now enchanted places which Mennonites were forced to leave as authoritative sites of Mennonite ethnicity. Instead, the text turns to the unacknowledged possibilities held by places and spaces that Mennonites find new, unfamiliar and even unwelcoming.
I shall discuss Wiebe’s novel and two other texts which reframe ideas of Mennonite ethnicity through shifts towards new spaces: Sandra Birdsell’s The Russländer (2001) and Wiebe’s short story “Finally, the Frozen Ocean” (2010), which brings characters from The Blue Mountains of China to places they only yearned for in that novel. These texts confirm Kulyk Keefer’s view that a writer of ethnicity is “forever coming across bones”, bones that carry the trace of history and of suffering that “we cannot not know” (“Coming Across”). Yet the texts are not only concerned with spaces bestowed with Mennonite bones, but also with new spaces that they yearn for, spaces which in Robert Kroetsch’s words raise “a doubt about [their] ability to know” (23). That precious doubt about previous ways of knowing does not erase bones from Mennonite history, but I will show it may enable Mennonite voices to know something new, to know more about themselves, and to reconcile what were once incommensurable ideas of history and ethnicity through engaging with space in new ways.
Land Deep in Time: Canadian Historiographic Ethnofiction